Woody plant decline in the Sahel of western Niger (1996–2017):is it driven by climate or land use changes?. (May 2022) - Hiernaux, Pierre; Adamou Kalilou, Amadou; Kergoat, Laurent; Brandt, Martin; Mougin, Eric; Fitts, Yasmin
Abstract: Although a recovery of woody vegetation has been observed throughout the Sahel, western Niger has not followed the overall satellite-derived greening trend. While satellite imagery can be used to study overall patterns and trends, only field observations can provide insights in the dynamics of woody plant populations. Here we used field data from 29 sites in the Dantiandou district in Niger to study woody species composition, plant density, crown cover, basal area, foliage and wood mass from 1996 to 2017. All sites show a decrease in woody plant parameters with a faster decrease in rangeland than in agricultural land. Most of the decrease is due to the loss of shrubs, while trees do not change significantly. When field observations were scaled up to the district level using land use maps, shrub density decreased from 342 to 155 ha −1 in agricultural land, and from 1567 to 250 ha −1 in rangeland. Trends in annual rainfall and soil moisture during the study period were not significant and cannot explain the decrease of woody vegetation. Instead, the expansion of cropped areas, shortened crop-fallow cycles and increasing pressure on wood resources to satisfy demand for fuel and construction materials may have contributed to the decline. Highlights: Woody plant density, crown and basal area decrease over 1996–2017 in West Niger. Woody plant cover assessed by remote sensing decreased gradually over 2000–2014. The rate of woody vegetation decrease is higher for rangeland than cropland. Cropland woody plant decrease is driven by cropping expansion and shorter fallow. Rangeland woody plant decrease is driven by more cutting for fuel wood.